Extending Query Translation to Cross-language Query Expansion with Markov Chain Models - Cao, Guihong; Gao, Jianfeng; Nie, Jian-Yun; Bai, Jing (CIKM, 2007)
Dictionary-based approaches to query translation have been widely used in Cross-Language Information Retrieval (CLIR) experiments. Using these approaches, translation has been not only limited by the coverage of the dictionary, but also affected by translation ambiguities. In this paper we propose a novel method of query translation that combines other types of term relation to complement the dictionary-based translation. This allows extending the literal query translation to related words, which produce a beneficial effect of query expansion in CLIR. In this paper, we model query translation by Markov Chains (MC), where query translation is viewed as a process of expanding query terms to their semantically similar terms in a different language. In MC, terms and their relationships are modeled as a directed graph, and query translation is performed as a random walk in the graph, which propagates probabilities to related terms. This framework allows us incorporating different types of term relation, either between two languages or within the source or the target languages. In addition, the iterative training process of MC allows us to attribute higher probabilities to the target terms more related to the original query, thus offers a solution to the translation ambiguity problem. We evaluated our method on three CLIR benchmark collections, and obtained significant improvements over traditional dictionary-based approaches.